Estudo investigativo de sinais iniciais de autismo: uma pesquisa com bebês irmãos de crianças autistas - Letícia Viana Pereira (2021)
Evidence indicates that many symptoms of autism are present in children before the first year of life. The detection of initial signs of autism before 18 months of life favors the intervention proposal. The general objective of this study was to describe and evaluate the occurrence of initial signs for Autism Spectrum Disorder (ASD) and risk signs for language acquisition in sibling babies of children diagnosed with ASD, considered at risk for also development the disorder. This is an epidemiological prospective analytical cohort study, which prospectively observed children aged 0 to 30 months who had at least one sibling diagnosed with ASD and aged over 30 months. The study was developed through the application of three protocols for evaluating signs risk for autism, child development and language acquisition. As the scientific community has come to value research with sibling babies of autistic children, in our first article we proposed to carry out a scope review, we were able to observe how the number of researches grows and a variability of "unusual" behaviors are found in this population. Issues related to social interaction, consequently to aspects of language development, are common points that present losses in siblings of children with ASD. In our second article we verified the statistical associations between protocols selected for research. Our experience with use of PREAUT-OLLIAC, IRDI, SEAL instruments in the assessment of children at risk for autism demonstrated a statistical association between them, suggesting a joint application for a complementary and unique analysis each case. In the third article, we aimed to analyze and describe the behavior of pragmatic ability siblings of autistic children and perform a correlation between the communicative profile obtained by the Pragmatics Protocol and the result of the SEAL Protocol, used to detect presence and/or absence of enunciative signs language acquisition. In assessment of children at risk for some developmental factor, results are expected that are not so positive, or that they fit within some diagnostic criteria. Our observation has shown that regardless of a predisposition to a developmental risk, babies can still summon, provoke, seek interaction and its continuation. The fourth article aimed to observe and describe the results of the application of instruments for initial identification of issues related to ASD and child development. Longitudinal follow-up allowed observe changes in the path of children and their families. The results of the second evaluations were better than those of the first evaluation. We can understand this finding from the fact that babies, like all of us, are constantly changing from our experiences. We affirm that with babies we learn more every day. We just have to be willing to listen them!